2021
DOI: 10.3390/diagnostics11101766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Advanta Dx SARS-CoV-2 RT-PCR Assay, a High-Throughput Extraction-Free Diagnostic Test for the Detection of SARS-CoV-2 in Saliva: A Diagnostic Accuracy Study

Abstract: Nasopharyngeal swab specimen (NPS) molecular testing is considered the gold standard for SARS-CoV-2 detection. However, saliva is an attractive, noninvasive specimen alternative. The aim of the study was to evaluate the diagnostic accuracy of Advanta Dx SARS-CoV-2 RT-PCR saliva-based assay against paired NPS tested with either NeumoDxTM SARS-CoV-2 assay or Abbott Real Time SARS-CoV-2 assay as the reference method. We prospectively evaluated the method in two settings: a diagnostic outpatient and a healthcare w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…All studies were published in 2020–2022 and were conducted in Argentina [31] , Belgium [32] , Bangladesh [33] , Brazil [14] , [34] , [35] , [36] , [37] , Canada [38] , [39] , [40] , [41] , [42] , Ethiopia [43] , France [44] , [45] , Greece [46] , India [47] , Iran [48] , Italy [49] , Japan [50] , [51] , [52] , [53] , Mexico [54] , [55] , Pakistan [56] , Philippines [57] , South Korea [58] , Thailand [59] , Turkey [60] , [61] , United Arab Emirates [62] , United Kingdom [63] , United States of America [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] . The total number of participants was 14,043, and the age varied between 18 and 106 years old.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published in 2020–2022 and were conducted in Argentina [31] , Belgium [32] , Bangladesh [33] , Brazil [14] , [34] , [35] , [36] , [37] , Canada [38] , [39] , [40] , [41] , [42] , Ethiopia [43] , France [44] , [45] , Greece [46] , India [47] , Iran [48] , Italy [49] , Japan [50] , [51] , [52] , [53] , Mexico [54] , [55] , Pakistan [56] , Philippines [57] , South Korea [58] , Thailand [59] , Turkey [60] , [61] , United Arab Emirates [62] , United Kingdom [63] , United States of America [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] . The total number of participants was 14,043, and the age varied between 18 and 106 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The total number of participants was 14,043, and the age varied between 18 and 106 years old. Twenty-two studies only included patients who had symptoms of COVID-19 [14] , [31] , [33] , [34] , [37] , [43] , [47] , [48] , [50] , [51] , [53] , [54] , [55] , [57] , [59] , [60] , [61] , [65] , [68] , [70] , [71] , [73] , seventeen studies included symptomatic and asymptomatic patients [32] , [35] , [36] , [38] , [39] , [41] , [42] , [44] , [45] , [46] , [49] , [58] , [62] , [63] , [64] , [66] , [69] , one study included only asymptomatic patients [52] , and four studies did not report these data [40] , [56] , [67] , [72] . Other sources of information regarding demographics, characteristics of the population, and characteristics of the samples are available in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes performance metrics for the primary study groups (left column) and lists supporting tabulations (right column) found in the Supplementary Materials. Papers generated by PubMed, other searches, and bibliographies of systematic reviews and meta-analyses comprised (a) 34 clinical evaluations of the use of RAgTs in communities (see Table S2); (b) 30 clinical evaluations of RAgTs applied in emergency medicine (emergency rooms and emergency departments), including 9 with results for pediatric patients [58,[65][66][67][68][69][70][71][72] (Table S3); and (c) 18 clinical evaluations [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] that reported results for PCR-based testing of saliva in community groups of strictly asymptomatic subjects (Table S4). No human subjects were involved in this research.…”
Section: Clinical Evaluationsmentioning
confidence: 99%